Establishment and application of a dual real-time PCR assay for differential detection of PiAdV-1 and PiAdV-2 among pigeons in China in 2022–2023 - Lu Chen; Jingjing Wang; Yufeng Liu; Yuteng Chen; Haiming Wang; Jinping Li; Wenming Jiang; Xiaohui Yu; Hualei Liu (PLoS ONE, 2025)
Pigeon virus diarrhea is very common in the clinic, which has caused great damage to the pigeon industry. Pigeon adenovirus constitutes a significant pathogen responsible for pigeon viral diarrhea. Among them, Pigeon adenovirus 1 (PiAdV-1) and Pigeon adenovirus 2 (PiAdV-2) are the most common adenoviruses discovered in pigeon diseases in recent years. Infection with these viruses is common in clinical settings, which makes differential diagnosis more difficult. At present, real-time PCR is one of the most widely used techniques for the identification and detection of pathogens. This study presents the development of a dual real-time PCR assay designed specifically for the detection of PiAdV-1 and PiAdV-2. The dual real-time PCR assay developed in this study demonstrated satisfactory specificity, sensitivity, repeatability, and reproducibility, while showing no cross-reactivity with unrelated pathogens. The limit of detection (LOD) for PiAdV-1 is 94.8 copies/µL, and the LOD for PiAdV-2 is 88.4 copies/µL. This method was then used to analyze 20 liver tissue samples collected from dead pigeons, and the results were verified by genome sequencing. To understand the current epidemic status of pigeon adenovirus in China, the dual real-time PCR method established in this study was used to detect 500 pigeon swab samples collected from 10 provinces in China from 2022 to 2023. The results showed that the positive rates of PiAdV detected by the real-time PCR was 27.00% (135/500). PiAdV-1 single infection was detected in 8 cases (1.6%), PiAdV-2 single infection in 123 cases (24.6%), and PiAdV-1 and PiAdV-2 co-infection in 4 cases (0.8%). This study established a valuable tool for differentiating between PiAdV-1 and PiAdV-2 in practical applications and provided significant insights into the prevalence of these viruses in China.